Ukrainian-german relationship in translation XX – beginning of XXI centuries: modern period and perspectives (on the translations of fictions) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
This article is devoted to ukrainian-german relationship in translation studies XX – beginning of XXI centuries. A retrospective review focuses on examples of fiction. Attention is drawn to individual of translators who transferred textes of Ukrainian writers into German.
Keywords: author; idiostyle; original; translation; translator